2016
DOI: 10.18632/oncotarget.10892
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity of the therapeutical response to gemcitabine and metformin

Abstract: Cancer heterogeneity and microenvironmental aspects within a tumor are considered key factors influencing resistance of carcinoma cells to distinct chemotherapeutical agents. We evaluated a high concentration of metformin in combination with gemcitabine on a syngeneic orthotopic mouse model using 6606PDA cells. We observed reduced tumor size and reduced cancer cell proliferation after three weeks of chemotherapy with either compound and noticed an additive effect between gemcitabine and metformin on tumor weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Surprisingly, few other publications support this point of view. Many publications describe that metformin plus gemcitabine treatment increases cell death in various pancreatic cancer cell lines when compared to the monotherapies 11 , 12 , 13 or describe other benefits of combining metformin with gemcitabine 10 , 14 - 17 . Only very few publications reported that metformin inhibits for example cisplatin induced apoptosis of cancer cell lines 18 or apoptosis in primary cells 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surprisingly, few other publications support this point of view. Many publications describe that metformin plus gemcitabine treatment increases cell death in various pancreatic cancer cell lines when compared to the monotherapies 11 , 12 , 13 or describe other benefits of combining metformin with gemcitabine 10 , 14 - 17 . Only very few publications reported that metformin inhibits for example cisplatin induced apoptosis of cancer cell lines 18 or apoptosis in primary cells 19 .…”
Section: Discussionmentioning
confidence: 99%
“…For evaluating the influence of hypoxia or normoxia on cell lines, the cells (covering about 15% of the well surface) were incubated with DMEM high glucose medium or DMEM high glucose medium containing therapeutic agents for 72 hours either in an Innova CO-48 incubator (New Brunswick Scientific Co, Edison Edison, USA) under 1 % oxygen supply or in an incubator with normoxic conditions. For evaluating the influence of pH-value on cell lines, the cells were incubated for another 48 hours with DMEM high glucose medium adjusted to pH 6.8 or pH 7.8 with 1M HCl or 1M NaOH as previously described 10 . The medium with pH 6.8 was also supplemented with 10 mM lactate (Sigma-Aldrich St Louis, MO, USA) in order to mimic lactate production in the carcinoma.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Little is known though about the character and function of stroma within PDAC metastases [43]. Zechner et al did find that, within primary tumors treated with a combination of metformin and gemcitabine, metformin better inhibited cancer cells near the desmoplastic stroma, whereas gemcitabine inhibited proliferation in cells distant to the stroma [48]. Hesler et al showed that CAFs serve as sources of CYR61 in co-culture models and induce chemoresistance by downregulating nucleoside transporters that mediate cellular uptake of gemcitabine [49].…”
Section: Role Of Stromal Cells In Chemoresistancementioning
confidence: 99%